Ответы и объяснения

  • nikitaaz
  • почетный грамотей
2013-07-24T16:12:56+00:00
(х2 – 4х + 4)(х2– 8х – 9) < 0.
х2 – 4х + 4=0             х2– 8х – 9
Д=0                           д=64+36=10^2
x= 4\2=2                    x= (8-+10)/2=9; -1
(x-2)(x-2)                    (x-9)(x+1)
-------------------------------------------------------------------
(x-2)(x-2)(x-9)(x+1)<0
метод интервалов
 (x-2)^2   (x-9)    (x+1)<0
   x<2      x<9    x<-1
    +             -                      -                             +
=====0======0=================0==============
        -1             2                                  9
нам нужны минусы
значит
x  пренадлежит  (-1;2) u (2; 9).